The impact of some anthropogenic activities on river Nile delta wetland ecosystems - Mohamed M El-Shazly (Global Journal of Ecology - Peertechz Publications, 2019)
The River Nile delta shallow lakes namely, Edku, Burullus and Manzala are natural wetland ecosystems, connected to fresh water sources at the south and to the open sea at the north. Throughout their relatively short geological and hydrological history, the lakes received unpolluted fresh water from the river Nile. Egyptians have begun practicing some form of water management for agriculture and transportation since about 5,000 years ago. As a result of agricultural and industrial development over the last century, the lagoons have been the end points of the last Egyptian use of the Nile water before flowing to the Mediterranean Sea; currently, the lakes receive fresh water from polluted drains inflow. In the present investigation, we studied some common characters of the lakes; including the accumulation of Cu, Zn, Cd, Pb, Mn, Fe, and Al in water, surface sediments, Tilapia zillii fish, and the common reed, Phragmites austrlis. Sampling was undertaken in May 2017. Six to 9 water samples were withdrawn from locations close to drains - lake and lake-sea connections for each of the three lakes. Surface sediments, tilapia fishes and P. australis specimens were sampled from three different localities along the southern edge of each of the studied lakes, where most of the anthropogenic activities occur. Analysis of variance (ANOVA) was carried out to compare the chemical properties of the water among the three lagoons. The lowest concentrations of all the tested metals were found in water, while the highest concentrations of the tested metals (except Zn) were detected in surface sediments. The highest concentration of Zn was found in tilapia fish muscles. However, the magnitudes of heavy metal concentrations in the living components of the lagoons (tilapia fish and the common reed) didn't follow the same pattern as in the nonliving components (water and sediments). In situ measurements demonstrated pH values in the alkaline side. The horizontal salinity gradient between northern and southern edges of the lakes is quite obvious. The concentrations of inorganic anions were measured at both lagoons - sea, and drains - lagoons connections. Some of the major chemical characters of lake waters were also analyzed. Accumulation of N-NO3 at the mouths of the drains connected to the lagoons indicated a poor autotrophic activity. The history of area degradation of the lagoons indicated that their area reduction had occurred before the construction of the oldest dam in Egypt. The current management of the lagoons was discussed.